2017
DOI: 10.22161/ijeab/2.4.38
|View full text |Cite
|
Sign up to set email alerts
|

A case of Dystocia due to Fetal Ascites in Murrah Buffalo

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…In contrast to cattle ( Bos taurus and B. indicus ), female buffaloes show a low predisposition towards dystocic births due to key anatomical differences, such as their pelvic and genital structure. The iliac area of buffaloes is larger than in cattle, and the fifth sacral vertebra is separated, allowing greater freedom of movement and a wider birth canal that facilitates expulsion of the fetus [ 40 , 41 ]. The morphology of the female buffalo’s reproductive tract includes longer, wider vaginal lips, and a small vaginal canal that dilatates easily to help complete labor in a shorter time than in cattle [ 40 ].…”
Section: Calvingmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to cattle ( Bos taurus and B. indicus ), female buffaloes show a low predisposition towards dystocic births due to key anatomical differences, such as their pelvic and genital structure. The iliac area of buffaloes is larger than in cattle, and the fifth sacral vertebra is separated, allowing greater freedom of movement and a wider birth canal that facilitates expulsion of the fetus [ 40 , 41 ]. The morphology of the female buffalo’s reproductive tract includes longer, wider vaginal lips, and a small vaginal canal that dilatates easily to help complete labor in a shorter time than in cattle [ 40 ].…”
Section: Calvingmentioning
confidence: 99%
“…One of the most common causes of dystocic births is maternal–fetal disproportion [ 41 ]. Srinivas et al [ 47 ] reported that 40.8% of dystocic births in female Murrah buffaloes are due to fetal factors, including oversized fetuses and abnormalities such as deformities, congenital and acquired diseases (e.g., hydrocephaly, ascites, anasarca, hydrothorax), and inadequate positioning in the birth canal.…”
Section: Calvingmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned by Purohit et al [ 11 ], calving complications, or dystocia, describe an event where the normal phases of parturition involve difficulties or are lengthened (more than 12 h), causing consequences for the mother and the newborn [ 52 ]. Compared to cattle ( Bos taurus , Bos indicus ), in water buffaloes, calving complications are reported less frequently (65.62% vs. 40.17%) due to the wide pelvic canal of the animals [ 11 , 53 ]. However, uterine torsion is the main cause of dystocia during the last stage of pregnancy [ 54 ], with rates of frequency of 53.57% [ 11 ] and as high as 83.33% [ 14 ].…”
Section: Calving Complication Behaviormentioning
confidence: 99%